INFLUENCE OF AVERAGE MARKET PRICE OF FERTILIZERS AND AGRICULTURAL CREDITS ON THE ACREAGE RESPONSE OF SUGARCANE IN NWFP - M. Niamatullah; K.U. Zaman; M. A. Khan (Journal of Animal and Plant Sciences, 2010)
The study makes an effort to measure economic influence of market retail sale price of fertilizers as well as the termwise agricultural credits on the sugarcane acreage in NWFP. In this regard, the time-series data have been used over a period of 17 years from 1991-92 to 2007-08. The statistical analysis has been done through Nerlovian Adjustment Model and Augmented Dickey Fuller Test. The results reveal that area under sugarcane crop have been tremendously expanded due to favourable market retail Price of fertilizers in proportional significance ratios [DAP (P<0.05), SSP (P<0.10), NP (P<0.05)] as well as the adequate provision of agricultural credits [short-term credits (SC) (P<0.05) and medium-term credits (MC) (P<0.01)]. Results revealed that sugarcane growers were successful in bringing the long run equilibrium output. Such development has resulted in meeting not only domestic consumption adequately in NWFP as well as in Punjab and Sindh provinces of the country, but more specifically it helped in reducing the burden of sugar import in the country
Keywords: Acreage; price of fertilizer; agricultural credits; Nerlovian Adjustment Model; sugarcane.